2005
DOI: 10.1111/j.1471-0528.2004.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Term Breech Trial on medical intervention behaviour and neonatal outcome in The Netherlands: an analysis of 35,453 term breech infants

Abstract: Objective To examine the effects of the Term Breech Trial on the medical behaviour of Dutch obstetricians and on neonatal outcomes. Design Retrospective observational study.Setting The Netherlands.Population Infants born at term in breech presentation in the Netherlands between 1998 and 2002, with birthweights 4000 g (n ¼ 33,024) and >4000 g (n ¼ 2429), respectively. Multiple pregnancies, antenatal death and major congenital malformations were excluded. Methods Data derived from the Dutch Perinatal Database we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(126 citation statements)
references
References 28 publications
2
118
0
5
Order By: Relevance
“…A review of the Dutch perinatal database showed that the rate of planned elective caesarean section for term breech changed from 49% in the 33 months prior to the publication of the Term Breech Trial to 80% in the 25 months afterwards. 9 The analysis included more than 33 000 infants. This change led to a halving of the perinatal mortality rates and rates of low Apgar scores, as well as the rates of birth trauma, which fell by three-quarters.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the Dutch perinatal database showed that the rate of planned elective caesarean section for term breech changed from 49% in the 33 months prior to the publication of the Term Breech Trial to 80% in the 25 months afterwards. 9 The analysis included more than 33 000 infants. This change led to a halving of the perinatal mortality rates and rates of low Apgar scores, as well as the rates of birth trauma, which fell by three-quarters.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials 4 (8,9,12,14) Concurrent cohort studies 2 (18,19) Non-concurrent cohort studies 20 (10,11,13,(15)(16)(17)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) After applying the inclusion and exclusion criteria, the evidence selected in the search and defined as randomized controlled trials (RCT) were subjected to an appropriate checklist for critical assessment (Table 3). Critical assessment of RCTs allows to classify them according to the Jadad score, so that Jadad < 3 trials are considered inconsistent (B), and those with scores ≥ 3, consistent (A).…”
Section: Type Of Publication Includedmentioning
confidence: 99%
“…3 Of these, an increasing number of primary cesarean deliveries are performed for breech presentation. 4 The reasons fewer women today opt for attempted external cephalic version (ECV) are less clear. Patient request and physician ambivalence may be involved, driven by the concern that even if successful, ECV may result in a cesarean.…”
mentioning
confidence: 99%